Specific cleavage of the retinoblastoma protein by an ICE-like protease in apoptosis. - Jänicke, R U (1996)
Interleukin 1beta-converting enzyme-like (ICE-like) proteases are important mediators of apoptosis in diverse cell types and organisms. However, the role of these proteases in apoptosis cannot be satisfactorily explained on the basis of the physiological functions of their known substrates. Here we show that the C-terminal 42 amino acid peptide of the retinoblastoma (Rb) protein, an important cell cycle regulator with a known anti-apoptotic function, is specifically cleaved off by an ICE-like protease in tumour necrosis factor (TNF)- and staurosporine-induced apoptosis. Cleavage of Rb induced by TNF was blocked in vivo and in vitro by two specific inhibitors of ICE-like proteases, and in vitro by a point mutation (Asp886 to Ala) within the ICE-like protease cleavage site of Rb, (883)DEAD(886). An antibody raised against the C-terminal 15 amino acid peptide of Rb recognized the full-length but not the cleaved form of Rb. The extent of Rb cleavage correlated directly with TNF-induced apoptosis in all tumour cell lines examined. Cleaved Rb bound cyclin D3 and inhibited the transcriptional activity of E2F-1, but failed to bind to the regulatory protein MDM2, which has been implicated in apoptosis. As Rb suppresses cell death and its C-terminus has important regulatory functions, our results suggest that Rb cleavage is an important event in apoptosis.